2020
DOI: 10.1186/s12885-020-6533-0
|View full text |Cite
|
Sign up to set email alerts
|

PDAC-ANN: an artificial neural network to predict pancreatic ductal adenocarcinoma based on gene expression

Abstract: Background: Although the pancreatic ductal adenocarcinoma (PDAC) presents high mortality and metastatic potential, there is a lack of effective therapies and a low survival rate for this disease. This PDAC scenario urges new strategies for diagnosis, drug targets, and treatment. Methods: We performed a gene expression microarray meta-analysis of the tumor against normal tissues in order to identify differentially expressed genes (DEG) shared among all datasets, named core-genes (CG). We confirmed the CG protei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…Recent data showed that early diagnosis could be possible through AI analysis of the transcription products of certain PDAC genes. These studies have reported sensitivity and specificity ranging from 88%-95% and 83%-95% respectively[ 58 , 59 ]. AI has also been utilized to match PDAC biological information with chemical properties of specific drugs in order to develop models capable of predicting response to these specific agents[ 60 , 61 ].…”
Section: Ai-assisted Analysis Of Pathological and Molecular Features mentioning
confidence: 99%
“…Recent data showed that early diagnosis could be possible through AI analysis of the transcription products of certain PDAC genes. These studies have reported sensitivity and specificity ranging from 88%-95% and 83%-95% respectively[ 58 , 59 ]. AI has also been utilized to match PDAC biological information with chemical properties of specific drugs in order to develop models capable of predicting response to these specific agents[ 60 , 61 ].…”
Section: Ai-assisted Analysis Of Pathological and Molecular Features mentioning
confidence: 99%
“…This algorithm can learn by themselves and produce the output that is not limited to the input provided to them. Another fascinating feature is that, even if a neuron is not responding or a piece of information is missing, the network can detect the fault and still produce the output [36,37]. In addition, ANN can perform multiple tasks in parallel without affecting the system performance.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Additionally, we evaluated gene expression as an input feature for ML and selected the most relevant genes for PDAC using SVM-RFE (Almeida et al, 2020), which provided a ranking for the genes. Then, each DEG was assigned an R s value (see Materials and Methods), which was used to further rank all genes.…”
Section: Identification Of Disease Genes and Drug Targets In Pdacmentioning
confidence: 99%
“…By applying ML algorithms to proteomics and other molecular data from The Cancer Genome Atlas (TCGA), two subtypes of pancreatic cancer can be classified (Sinkala et al, 2020). A meta-analysis of PDAC microarray data could help predict biomarkers that can be used to build AI-based computational predictors for classifying PDAC and normal samples (Bhasin et al, 2016), as well as predicting sample status (Almeida et al, 2020). To predict and validate novel drug targets for cancer, including PDAC, a ML-based classifier that integrates a variety of genomic and systems datasets was built to prioritize drug targets (Jeon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%